Answer:
0
Step-by-step explanation:
-7+1+ -1 * -6
Using PEMDAS, we multiply and divide first
-1*-6 = 6
Then we add and subtract from left to right
-7+1+ 6
-6+6 =0
Okay so $14,000 is the equivalent of 6/5ths
so divide $14,000 by 6= $2333.3r
you need 5/5
so $2333.3r x 5 = $11666.67
this is the original price
Answer:
The answer is C
Step-by-step explanation:
We have f(x) function as below:
![f(x)=(2x-3)^3](https://tex.z-dn.net/?f=f%28x%29%3D%282x-3%29%5E3)
and the converted function g(x) is as mentioned below:
![g(x)=(-2x+3)^3](https://tex.z-dn.net/?f=g%28x%29%3D%28-2x%2B3%29%5E3)
We can observe that:
f(x)=-g(x)
Therefore it can be said that this function reflected horizontally.
Note: please check the plot attached.
Answer:
24+70+56=150
Step-by-step explanation: